The Role of Financial Performance in The Relationship Between Human Resource Accounting Disclosure and Company Value - Siti Alya Noviani; Siti Sundari; Tantina Haryati (Economics and Business Journal (ECBIS), 2026)
This study aims to analyze the effect of Human Resource Accounting (HRAC) disclosure on firm value, with financial performance as a mediating variable. This quantitative study uses secondary data in the form of annual reports and sustainability reports from 14 companies during the 2020–2024 period, with a total of 70 observations. HRAC disclosure is measured using the Human Resource Disclosure Index through a content analysis approach. Firm value is proxied by Net Asset Value (NAV) transformed into the natural logarithm, while financial performance is measured using ROA. Data analysis was performed using path analysis with SPSS software, and the Sobel test to examine the role of financial performance as a mediating variable. The results show that HRAC disclosure affects firm financial performance, but does not directly affect firm value. Financial performance is proven to affect firm value in a negative direction. The results of the Sobel test indicate that financial performance plays a significant role as a mediating variable in the relationship between HRAC disclosure and firm value. These findings indicate that HRAC disclosure affects firm value indirectly through financial performance. ASDM disclosure functions as supporting information and additional signals for investors, but is not yet able to become the main determinant in the direct formation of company value.